Avian Paramyxovirus Serotype-1: A Review of Disease Distribution, Clinical Symptoms, and Laboratory Diagnostics - Nichole L. Hines; Cathy L. Miller (Veterinary Medicine International)
Avian paramyxovirus serotype-1 (APMV-1) is capable of infecting a wide range of avian species leading to a broad range of clinical symptoms. Ease of transmission has allowed the virus to spread worldwide with varying degrees of virulence depending on the virus strain and host species. Classification systems have been designed to group isolates based on their genetic composition. The genetic composition of the fusion gene cleavage site plays an important role in virulence. Presence of multiple basic amino acids at the cleavage site allows enzymatic cleavage of the fusion protein enabling virulent viruses to spread systemically. Diagnostic tests, including virus isolation, real-time reverse-transcription PCR, and sequencing, are used to characterize the virus and identify virulent strains. Genetic diversity within APMV-1 demonstrates the need for continual monitoring for changes that may arise requiring modifications to the molecular assays to maintain their usefulness for diagnostic testing.